2015
DOI: 10.1007/s00268-015-3365-1
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Acute Cholecystitis and Risk of Iatrogenic Bile Duct Injury During Cholecystectomy, a Population‐Based Case–Control Study

Abstract: Patients with on-going acute cholecystitis had twice the risk of sustaining a biliary lesion compared to patients without acute cholecystitis. There was a relation between the Tokyo guidelines severity grading of acute cholecystitis and injury risk and the intention to use intraoperative cholangiography halved the risk of reconstructed bile duct injury during cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 40 publications
1
58
2
6
Order By: Relevance
“…Other studies have reported BDI rates of 0.62–0.9% for LC and 0.38–1.24% for OC [2628]. These studies were however not homogenous for acute cholecystitis for which the risk of BDI has been reported as twice as high compared with patients who undergo cholecystectomy electively [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported BDI rates of 0.62–0.9% for LC and 0.38–1.24% for OC [2628]. These studies were however not homogenous for acute cholecystitis for which the risk of BDI has been reported as twice as high compared with patients who undergo cholecystectomy electively [29]. …”
Section: Discussionmentioning
confidence: 99%
“…These include difficulties at the patient level such as inability to schedule and keep appointments and at a systems level where referrals may or may not be appropriately made to surgical outpatients. 22 Recurrent episodes of acute biliary pain that occur whilst awaiting operative management may result in pericholecystic adhesions which may contribute to technical difficulties and surgical morbidity. 19 The detrimental effects of biliary colic affect patients, the healthcare network and society.…”
Section: Discussionmentioning
confidence: 99%
“…A complex or prolonged operation may result from unexpected intra‐operative findings that cannot be dealt with by on‐call surgeons or trainees who do not have the requisite skills or experience. Severe inflammation around the gallbladder (GB) can make safe dissection difficult, and may increase the risk of both minor and major complications . When an early LC policy is adopted for patients with acute biliary presentations it would be helpful to predict the degree of operative difficulty.…”
Section: Introductionmentioning
confidence: 99%